Aerolysin nanopore-based identification of proteinogenic amino acids using a bipolar peptide probe. Issue 18 (23rd August 2022) - Ge, Yaxian; Cui, Mengjie; Zhang, Qiuqi; Wang, Ying; Xi, Dongmei
Abstract : Nanopore technology has attracted extensive attention due to its rapid, highly sensitive, and label-free performance. Abstract : Nanopore technology has attracted extensive attention due to its rapid, highly sensitive, and label-free performance. In this study, we aimed to identify proteinogenic amino acids using a wild-type aerolysin nanopore. Specifically, bipolar peptide probes were synthesised by linking four aspartic acid residues to the N-terminal and five arginine residues to the C-terminal of individual amino acids. With the help of the bipolar peptide carrier, 9 proteinogenic amino acids were reliably recognised based on current blockade and dwell time using an aerolysin nanopore. Furthermore, by changing the charge of the peptide probe, two of the five unrecognized amino acids above mentioned were identified. These findings promoted the application of aerolysin nanopores in proteinogenic amino acid recognition.